Embedding and sustaining change in technology-enhanced education: lessons learned from a cross-institutional transformation project - Andrew Comrie; Morag Gray; Terry Mayes; Keith Smyth (Education in the North, 2010)
Tertiary educational institutions, and particularly Universities, face many strategic challenges arising from increasing globalisation, the widening access agenda, demand for more flexible provision, and meeting increasingly diverse students needs while providing an engaging education that equips students for their chosen professions and to be lifelong learners. We are now in an informed position regarding what current and emerging technologies can potentially offer by way of responding to these challenges. Yet for many institutions, and the educators within them, there remain significant issues around understanding how to approach technology-enhanced education in ways that build upon existing good practice, and in ways that can help us to change and even radically transform learning and teaching so as to better position our institutions to address the aforementioned challenges. This paper describes the nature and impact of the cross-institutional TESEP (Transforming and Enhancing the Student Experience through Pedagogy) project. TESEP aspired to take forward institutional practice in technology-enhanced education in a truly transformative way, underpinned by a pedagogy-first, technology-second philosophy. Through exploring the pedagogic principles, staff development approaches and strategic initiatives that were central to the project, this paper tackles the core issues TESEP had to address, and through case examples highlights the benefits a project like TESEP might bring. Particular consideration is given to the key lessons that were learned in how to sustain institutional and crossinstitutional change beyond the formal lifetime of such an initiative.